A New Toolbox to Label Zinc-MTF1 Responsive Neuronal Populations Unravels Cellular Congruence between MTF1 Responses and T-type Calcium Channelopathies in an Experimental Model of Epilepsy - Annachiara Meconi; Katharina Schmied; Aniella Bak; Julika Pitsch; Henner Koch; Susanne Schoch; Albert J. Becker; Karen M. J. van Loo (Molecular Neurobiology, 2026)
Temporal lobe epilepsy (TLE) is one of the most common forms of epilepsy and usually manifests after serious brain insults, including traumatic brain injury, stroke, and status epilepticus (SE). Previously, we identified a new epilepsy-associated transcriptional control mechanism that relies on the zinc-dependent transcriptional activator metal-regulatory transcription factor-1 (MTF1). MTF1 is one of the key transcription factors involved in intracellular metal ion balance. Upon excessive increase in the concentration of zinc in the cytoplasm, zinc can bind to MTF1, inducing its translocation to the nucleus to activate the expression of metal-response element (MRE)-containing genes, including metallothioneins and the T-type calcium channel Ca V 3.2. To date, in-depth analyses of MTF1 downstream signaling cascades have been limited by the lack of tools to visualize Zn 2+ /MTF1-responsive neuronal activation in vivo . To overcome this challenge, we developed a transcriptional reporter unit that enables genetic labeling of Zn 2+ /MTF1-expressing cells in vitro , ex vivo and in vivo . Applying this new toolbox in a mouse model for epileptogenesis revealed a clear overlap between Zn 2+ /MTF1-induced cellular localization and activity of a promoter-driven reporter for Ca V 3.2, supporting the calcium channel as a direct target of the Zn 2+ /MTF1-cascade. This innovative toolbox provides a powerful resource for studying zinc-induced MTF1 activation in both physiological and pathological processes, including epileptogenesis.